2005
DOI: 10.1617/14104
|View full text |Cite
|
Sign up to set email alerts
|

Mode I and mixed mode fracture studies in brittle materials using the Brazilian disc specimen

Abstract: High Strength Cement Mortar (HSCM) with very fine sand exhibits a typical brittle behavior. In the present work, a linear elastic fracture mechanics based model is used for the fracture studies conducted On this material. The experimental testing program is based on the diametral compression test of disc specimens containing an internal slant crack. Under the Mode I loading condition, the test method which has been previously used is applied to determine the critical value of the stress intensity factor, Klo f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 0 publications
4
18
0
Order By: Relevance
“…Krishnan et al [4], Khan and Al-Shayea [5], Chang et al [6], Al-Shayea [7], Ayatollahi et al [8], Lanaro et al [9] have also used the CSTBD specimen to determine mixed mode fracture toughness of various rock types. Yamauchi [34] and Atahan [35] have conducted a series of mixed mode fracture toughness experiments on graphite and concrete using the CSTBD specimen. The frequent use of this specimen makes it essential to propose an appropriate criterion for estimating the values of mode I and mode II fracture toughness which are obtained from the CSTBD specimen.…”
Section: Resultsmentioning
confidence: 99%
“…Krishnan et al [4], Khan and Al-Shayea [5], Chang et al [6], Al-Shayea [7], Ayatollahi et al [8], Lanaro et al [9] have also used the CSTBD specimen to determine mixed mode fracture toughness of various rock types. Yamauchi [34] and Atahan [35] have conducted a series of mixed mode fracture toughness experiments on graphite and concrete using the CSTBD specimen. The frequent use of this specimen makes it essential to propose an appropriate criterion for estimating the values of mode I and mode II fracture toughness which are obtained from the CSTBD specimen.…”
Section: Resultsmentioning
confidence: 99%
“…carried out a set of combined mode fracture toughness tests on a newly developed structural material called high strength cement mortar (HSCM) using CCBD samples. This material has very fine grains and fails in a brittle manner when subjected to mechanical loading 1 . However, the experimental results obtained from fracture tests on the HSCM specimens do not comply with the theoretical predictions.…”
Section: Introductionmentioning
confidence: 92%
“…However, the nonlinear region in some of the quasi‐brittle materials like rocks and fine grain cement mortars or in large structures like dams are very often small relative to the characteristic dimensions of the cracked component (like the crack length, specimen thickness, ligament, etc.). For such cases, the components are usually susceptible to brittle fracture due to sudden extension of their inherent cracks and their fracture behaviour can still be investigated by means of LEFM principles 1–6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile many studies were carried out [12] on fracture toughness of self-compacting concrete. Recent publications [13,14] have shown that fracture mechanics has now been established as a fundamental approach that can explain certain nonlinear aspects of concrete behaviour, help to prevent This paper uses tow approaches to analyze the crack propagation of cracks three-point bending concrete beam and Brazilian disk with initial crack based on determination of stress intensity factor analytically starting from weight functions [15] and numerically using the finite element software platform Abaqus, and compares with the features in simulating soften behaviour for various concrete fracture models.…”
Section: Introductionmentioning
confidence: 99%